What I told my daughter : lessons from leaders on raising the next generation of empowered women - Tassler, Nina; Littleton, Cynthia (Atria Books, 2016)
A "diverse group of women--from Madeleine Albright To Ruth Bader Ginsburg, from Dr. Susan Love to Whoopi Goldberg and more...reflect on the best advice and counsel they have given their daughters either by example, throughout their lives, or in character-building, teachable moments between parent and child."--Book jacket.